The Genesis of the Private Financial Control in Ancient Russia - A. E. Krioni (Учёт. Анализ. Аудит)
To search the roots of historical institutions in deep antiquity is a way which is completely justified and even necessary. However, it so happens that sometimes under new conditions even the most ancient phenomena undergo such strong transformations that their initial characteristics could not be found by simple reading of historical documents of law. One of these phenomena, according to the author, seems to be the institute of the Old Russia’s private audit to be visibly found in the financial life of the Slavs after a deep examination of trade customs and traditions of making deals. Such acts as “Zaklich”, “The Commandment on Bargaining” in Oustav of the Grand Prince Jaroslav Vlademerich of Sudh, article 27 of the section “On Chelyadins” in Pravda Rouskaya and similar provisions included in the Code of Trade Law describe the procedure which makes us admit that private control in Ancient Russia existed.